2004
DOI: 10.1359/jbmr.040820
|View full text |Cite
|
Sign up to set email alerts
|

Bone Fragility and Collagen Cross-Links

Abstract: Infrared imaging analysis of iliac crest biopsy specimens from patients with osteoporotic and multiple spontaneous fractures shows significant differences in the spatial variation of the nonreducible: reducible collagen cross-links at bone-forming trabecular surfaces compared with normal bone.Introduction: Although the role of BMC and bone mineral quality in determining fracture risk has been extensively studied, considerably less attention has been paid to the quality of collagen in fragile bone. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
182
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(196 citation statements)
references
References 49 publications
11
182
1
2
Order By: Relevance
“…Genotype differences in serum pyridinoline content were not seen in this study. The significance of this finding is unclear as previous studies have found both increased and decreased crosslinking in oim/oim animals, although crosslinking characteristics are unique to the tissue containing them [13,53,54]. The combination of age-associated accumulation of both mineral and organic phases of the bone and a decrease in bone turnover may account for the increase in biomechanical integrity of bone with age.…”
Section: Discussionmentioning
confidence: 84%
“…Genotype differences in serum pyridinoline content were not seen in this study. The significance of this finding is unclear as previous studies have found both increased and decreased crosslinking in oim/oim animals, although crosslinking characteristics are unique to the tissue containing them [13,53,54]. The combination of age-associated accumulation of both mineral and organic phases of the bone and a decrease in bone turnover may account for the increase in biomechanical integrity of bone with age.…”
Section: Discussionmentioning
confidence: 84%
“…These samples also showed increased osteoid thickness and volume fraction in the histomorphometric measurements compared with the normal samples. Indeed, the trabecular edges were less mineralized than normal bone.Previously, FTIRI has been employed to study osteoporotic bone (17,19,27) or bone from patients with fragility fractures, (15) as well as bone from patients with ostemalacia. (18) However, to our knowledge, no previous studies have employed FTIRI to investigate bone from patients with ROD.…”
mentioning
confidence: 99%
“…Additionally, in the previously published study no strict tissue age normalization was employed, thus the reported results are expected to be dependent on bone turnover. (11) Finally, it has been previously reported that there are significant differences in the intrinsic material properties between normal and osteoporotic human bone, (36)(37)(38) thus extrapolation from normal canine to osteoporotic human bone, although informative, may not be conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…(10,11,37,38) It should be noted that in cases for which bone strength and BMD exhibit divergent trends, the mineral maturity/crystallinity and collagen cross-links ratio correlate with the former rather than the latter. (38,57) It has recently been shown in animals that alterations in collagen cross-links (most notably the pyr/divalent cross-link ratio), coupled with changes in microarchitecture, are sufficient to adversely affect bone biomechanical performance in the absence of any concomitant changes in mineral quantity and quality, even when these changes are anatomically confined to bone-forming surfaces. (61) Both shorter-term and longer-term RIS use resulted in significantly lower pyr/divalent collagen cross-link ratios compared to ALN, in agreement with a recent publication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation